"Population structure of Drug-Susceptible, -Resistant and ESBL-producing Escherichia coli from Community-Acquired Urinary Tract Infections". Issue 1 (December 2016) - Hertz, Frederik; Nielsen, Jesper; Schønning, Kristian; Littauer, Pia; Knudsen, Jenny; Løbner-Olesen, Anders; Frimodt-Møller, Niels
Abstract Background Escherichia coli is the most common cause of urinary tract infection (UTI). The pathogenic isolates are becoming increasingly resistant to antibiotics; with a worldwide dissemination of resistant sequence types (ST). We characterized three different uropathogenicE. coli populations, from non-hospitalized patients to describe the genetic kinship between resistant and susceptible isolates. We studied the populations by use of multi-locus sequence typing (MLST) and abbreviated-multi locus variable number of tandem repeat analysis (a-MLVA). Urine samples submitted for testing, by general practitioners, were identified at Dept. of Clinical Microbiology at Hvidovre Hospital, Denmark, from Oct. 2011 to July 2012. We included 94 fully susceptible, 94 resistant (non-ESBL) and 98 Extended Spectrum Beta-lactamases- (ESBL)-producingE. coli isolates. Results The ESBL population was dominated vastly by ST131 (51 %), ST38 (9 %) and ST69 (6 %). In the resistant group ST69 (18 %), ST73 (11 %) and ST131 (15 %) were the largest clusters. In the susceptible population more STs and a-MLVA codes were identified compared to the other groups and ST73 and ST95 were found as the only clusters with 16 % and 6 %, respectively. Ninety-eight per cent of the ESBL-producingE. coli isolates were CTX-M-producers. Conclusion ST131 dominated the population of community-associated uropathogenic ESBL-producingE. coli, but was less frequent among non-ESBL-producingE. coli. The fully susceptibleE. coli population was a much more diverse group than the resistant and ESBL-producingE. coli populations. Overall, these findings suggest that dominant ESBL-producing lineages are derived from UPEC lineages already established in the general UPEC population.